Neonatal morbidity and mortality of sick newborns admitted in a teaching hospital of Uttarakhand - Ritu Rakholia; Vineeta Rawat; Mehar Bano; Gurpreet Singh (Wolters Kluwer Medknow Publications, 2014)
Context: India accounts for 27.3% of total neonatal deaths in the world. This rate is highest in poor and marginalized areas like hilly regions of Uttarakhand that lack medical facilities. The newborns referred from here and admitted as outborn neonates contribute to the high neonatal mortality rate (NMR) of India. Aims : To study the demographic profile and morbidity-mortality pattern of neonates admitted in Sick Neonatal Care Unit (SNCU) and study the difference between inborn and outborn neonates. Study Design: Retrospective study of medical records for 1 year (2013-2014). Subjects and Methods: The age, sex, gestational age, and morbidity and mortality profile of all SNCU admissions in 1 year was determined, and the difference between inborn (those born in Teaching Hospital) and outborn (neonates delivered outside and referred) was calculated. Modifiable risk factors to reduce NMR in Uttarakhand were determined. Statistics: The data were analyzed using appropriate statistical tools in software Statistical Package for the Social Sciences (SPSS)-18. Results : Of the 721 neonates admitted, 63.25% neonates were males, and 53.54% were outborn and 46.46% inborn. Approximately, 60% were low birth weight and 50% preterm. Respiratory distress syndrome (RDS) (21.9%), sepsis (19%), perinatal asphyxia (16.37%), and jaundice (12.9%) were the chief morbidities. The chief causes of mortality were prematurity (25.6%), sepsis (21.6%), perinatal asphyxia (19.5%), and RDS (17.3%) with a statistically higher rate in the outborn in comparison with inborn. Total 20.5% neonates died due to poor outcome of outborn neonates. Conclusion: Huge burden of neonatal death among the outborn is due to preventable causes like asphyxia and infections in Uttarakhand. Health policies must ensure increased access to essential services to target sick neonates born here.